Tender Conspiracy Under KPPU Decision and Prohibition of Monopolistic Practices Act - Udin Silalahi; Priskilla Chrysentia (Sriwijaya Law Review, 2020)
Tender conspiracy is one of the anti-competition acts prohibited under Article 22 Law No. 5 of 1999 on Prohibition of Monopolistic Practices and Unfair Business Competition. As one of the violations which are almost always injurious, tender conspiracy is only regulated by a rule of reasonable approach giving an interpretation room of the consequences of the violation. The tender conspiracy is also proven conducted by reported parties in the case that it had been decided by KPPU, such as in the KPPU Decision Number 06/KPPU-L/2015. The questions arising in connection with the rampant practices of tender conspiracy are how they regulate in the applicable law and how KPPU decides on the practice of tender conspiracy in the case concerned with the law. The aim is to examine the causes of the rampant practice of tender conspiracy in relation to the regulations governing it, as well as to review the KPPU's decision on real tender conspiracy case. For this reason, this research is normative legal research with qualitative analysis techniques on secondary data and uses the statute approach, and case approaches. The results of the study indicate that Article 22  is not sufficient yet to regulate the prohibition of tender conspiracy and often leads to multi-interpretation. the KPPU decided that there is a horizontal conspiracy among defendantsindetermining of the tender winner